The Measurement of Satisfacation Rate between Rehabilitatio Services Clients in the Tehran\'s Red Crescent - Behrad Razavi-Alhashem; Ali Reza Mohseni-Tabrizi; Mehdi Rahgozar (University of Social Welfare and Rehabilitation Sciences, 2008)
Objective: The aim of this investigation is to measure the satisfaction rate between rehabilitation centers of the red crescent organization in Tehran city. This investigation attemps to gain access to his strength and weakness points in the organization, and helps to progress the quality and efficiency of the rehabilitation services. Materials & Methods: This study has been done as descriptive and survey methods. Data collection was done by using the produced- investigator questionnaire. Its reliability was measured 0.82. Sample sizes were 190 persons from the rehabilitation centers clients in Tehran's Red Crescent that were selected by cluster sampling. Data were analyzed by use of Chi-square, independent T test and variance analysis.  Results: The findings showed that there is significant relationship between participation rate in the treatment process and clients satisfaction (P=0.021), Also, there is significant relationship between the efficiency of rehabilitation equipments and their satisfaction (P=0.002), between rehabilitation service quality and satisfaction (P<0.001) and between behavior and contact of personnel with clients satisfaction (P<0.001). Conclusion: The results showed that rehabilitation services by influence of different factors led to reduce client's satisfaction. The satisfaction could be introduced as fanction of the client participation rate in treatment process, service efficiency and quality rate and behavior type and personnel contacts (such as physician, technicians and etc). Then, by doing short-time educational terms for personnels, to equip centers by proper rehabilitation possibilities, to inform and to provide clients participation from treatment process, can to meet clients and their family's expectations and to increase their satisfaction.